Synthesis, modification strategies and applications of coal-based carbon materials - Li, Hongqiang; He, Xiaojun; Wu, Tingting; Jin, Biyu; Yang, Lei; Qiu, Jieshan (Fuel processing technology, 2022)
Coal is one of the natural materials with three-dimensional (3D) cross-linked network structure composed of aromatic units and hydroaromatic groups. The unique molecular properties of coal and its derivatives endow them with great potential as resources to synthesize functional carbon materials. Up to date, much progress has been made in coal-based functional carbon materials in the past two decades, which need to be comprehensively summarized with an aim of streamlining and clarifying the future directions in the fabrication of functional carbon materials from coal and its derivatives. Here, the recent progresses in the synthesis of coal-based carbon materials (CCMs), including porous carbons, fullerenes, carbon nanotubes, carbon spheres, carbon fibers, graphene and carbon dots are summarized. The modification strategies of CCMs are also summarized, which are crucial to tune the structure and properties of the CCMs in terms of their applications. Finally, the perspectives and the future developments of CCMs are discussed. This comprehensive review may shed a new light on the design and production of coal-based functional carbon materials for applications in energy storage, catalysis, composites materials, and environment protection. Recent progresses in the synthesis, modification strategies and potential applications of coal-based carbon materials have been reviewed. The perspectives of coal-based carbon materials are highlighted. [Display omitted] •Recent progresses in the synthesis and modification strategies of coal-based carbon materials are summarized.•The applications and potentials of coal-based carbon materials are highlighted.•The perspective and new research directions of coal-based carbon materials are pointed out.